Effects of response preference on resistance to change. Issue 1 (10th January 2018) - Ringdahl, Joel E.; Berg, Wendy K.; Wacker, David P.; Crook, Kayla; Molony, Maggie A.; Vargo, Kristina K.; Neurnberger, Jodi E.; Zabala, Karla; Taylor, Christopher J.
Abstract : Treatments based on differential reinforcement of alternative behavior, such as functional communication training, are widely used. Research regarding the maintenance of related treatment effects is limited. Nevin and Wacker (2013) provided a conceptual framework, rooted in behavioral momentum theory, for the study of treatment maintenance that addressed two components: (a) reemergence of problem behavior, and (b) continued expression of appropriate behavior. In the few studies on this topic, focus has been on variables impacting the reemergence of problem behavior, with fewer studies evaluating the persistence of appropriate behavior. Given the findings from applied research related to functional communication training, variables related to response topography, such as response preference, may impact this aspect of maintenance. In the current study, the impact of response preference on persistence was evaluated in the context of functional communication training for individuals who did not exhibit problem behavior (Experiment 1) and for individuals with a history of reinforcement for problem behavior (Experiment 2). High‐preferred mands were more persistent than low‐preferred mands. These findings suggest that response related variables, such as response preference, impact response persistence and further suggest that response related variables should be considered when developing interventions such as functional communication training.